Optimalisasi Peran Direktorat Jendral Kekayaan Negara dalam Mewujudkan Tata Kelola Barang Milik Negara yang Transparan dan Akuntabel - Keyka Nazfidza Labuhane; Abdul Rahman (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This study aims to analyze the role of the Directorate General of State Assets (DJKN) in realizing transparent and accountable management of State Assets (BMN). Good management of BMN is one of the keys to increasing the efficiency of state finances and encouraging professional and integrated governance. Transparency and accountability in the management of BMN are not only administrative demands, but also important instruments in building public trust in the management of state assets. This study uses a descriptive qualitative method with data collection techniques through literature studies and documentation. Data sources were obtained from laws and regulations, official DJKN documents, audit reports, and scientific publications related to BMN management. The results of the study show that DJKN has made various efforts to increase transparency and accountability, including through the development of technology-based information systems, preparation of accurate BMN reports, increasing human resource capacity, and strengthening supervision. However, there are still a number of challenges such as data disorder, limited human resources, and weak synergy between agencies. Therefore, an integrated and sustainable strategy is needed to optimize the role of DJKN in the future.